Argentina : Technical Assistance Report-Technical Assistance Mission on External Sector Statistics (November 14-25, 2016). - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2019)
At the request of the National Institute of Statistics and Censuses (INDEC), a technical-assistance mission on external-sector statistics (ESS) visited Buenos Aires on November 14-25, 2016. Currently, INDEC's National Directorate for International Accounts (DNCI) compiles and disseminates ESS following the guidelines of the fifth edition of the Balance of Payments Manual. The mission reviewed the ESS methodology, data sources, and dissemination policy in order to help enhance its quality and to assist compilers in migrating the methodology to the sixth edition of the Balance of Payments and International Investment Position Manual (BPM6). The main data sources used to compile the current account and the capital account (excluding investment income, which is compiled along with the financial account and the IIP) are customs records, corporate surveys, the international-tourism survey, accounting information available to the public, administrative records, and information concerning the exchange balance disseminated by the Central Bank of Argentina (BCRA). The mission found data sources and compilation procedures to be sound. Although the mission identified improvements that could add to the quality of certain estimates, the balances of the current and capital accounts are expected to remain substantially unchanged.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet